2021
DOI: 10.3390/ijerph181910189
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the Predictors of Community Acceptance of Waste Incineration Plants in Urban China: A Qualitative Analysis from a Public Perspective

Abstract: Due to concerns about consequences to public health, the ecosystem, the natural landscape etc., the planning and construction of waste incineration plants always gives rise to a reaction and even protests from local communities. This study aims to investigate the determinants affecting public acceptance of waste incinerators. We contribute to the existing knowledge in the following ways: (1) this study undertook a qualitative analysis on community acceptance of nimby facilities in the context of China for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…A qualitative study in China found positive views between governments and citizens and the importance of perceived justice and political efficacy. WIPs are usually opposed by the public as they are perceived to be NIMBY facilities but this qualitative study did not test the hypothesis of distance because all respondents were the residents near WIPs (Zhang et al 2021). A study in northern China also found that trust towards WIPs among the residents living in the vicinity of WIPs was a significant factor influencing residents' perceptions (Huang et al 2022).…”
Section: Discussionmentioning
confidence: 88%
“…A qualitative study in China found positive views between governments and citizens and the importance of perceived justice and political efficacy. WIPs are usually opposed by the public as they are perceived to be NIMBY facilities but this qualitative study did not test the hypothesis of distance because all respondents were the residents near WIPs (Zhang et al 2021). A study in northern China also found that trust towards WIPs among the residents living in the vicinity of WIPs was a significant factor influencing residents' perceptions (Huang et al 2022).…”
Section: Discussionmentioning
confidence: 88%
“…These statements cover a variety of categories and sub-categories representing perceptions on waste incineration plants: risk perception, interest, justice (procedural justice, interactive justice, distributive justice); political efficiency; social trust (local government trust, waste incineration plant trust); place attachment; and knowledge level. The Q-set employed in this study represents the theoretical and practical foundation ( Zhang, 2021 ). The specific items of the Q statements are shown in Table 1 .…”
Section: Methods Data and Analysismentioning
confidence: 99%
“…For China, NIMBYism was widely known to the public after the beginning of the 21st century. One piece of statistical data shows that complaints about environmental issues increased by 29% every year since 1996 in China [ 23 ]. The emergence of the anti-growth alliance in China can be attributed to several factors.…”
Section: Literature Reviewmentioning
confidence: 99%